Laser for vascular anomalies: successful outcomes in children. (1st March 2020) - Rinaldi, G.; Batul Syed, S.
Abstract: Vascular anomalies can cause both emotional and physical distress to patients, particularly children. The paediatric laser service at Great Ormond Street Hospital (GOSH) treats a range of dermatological conditions including a variety of vascular anomalies, excess hair growth and disfiguring scars. The laser team at GOSH has 25 years of experience in treating a wide variety of paediatric dermatological conditions using various laser therapies. With over 600 new referrals for laser therapy and over 1000 laser procedures each year the GOSH laser team has vast amounts of experience with both common and rare conditions. Excellent clinical outcomes continue to be delivered, and new treatment therapies are constantly being developed to treat more recalcitrant lesions. The adverse effect rates experienced by the GOSH laser patients have been decreasing over the past two decades, reaching the low rate of 0.8% per treated patients per year. This remarkable achievement has been continuously improved by integrating specific and standardized laser protocols for each patient treated, to ensure efficacious and safe laser treatment delivery. Treating vascular anomalies with laser therapy creates significant positive results among the paediatric population, thus laser therapy at GOSH makes a significant impact upon children's lives with both rare and common vascular anomalies. Abstract : Click here for the corresponding questions to this CME article.